Comparing the Effectiveness of Forgiveness Training and Mindfulness Training on Cognitive Flexibility and Communication Skills in Individuals with Substance Use Disorders - Nakhaee, Alireza; Arab, Ali; Rostami, Masoud (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The primary objective of this study was to compare the effectiveness of forgiveness training and mindfulness training on cognitive flexibility and communication skills in individuals with substance use disorders (SUDs). Methodology: A quasi-experimental design with pre-test, post-test, and follow-up measurements was employed. The study involved 45 participants with SUDs, randomly assigned to three groups: a forgiveness training group, a mindfulness training group, and a control group, with 15 participants in each group. Both interventions were delivered over 12 weeks, with cognitive flexibility and communication skills assessed at three time points using validated questionnaires. Data were analyzed using repeated measures ANOVA, with Bonferroni post-hoc tests to identify significant differences between groups and over time. Findings: The repeated measures ANOVA indicated significant effects of group membership on cognitive flexibility (F(2, 42) = 17.140, p < .001, η² = .449) and communication skills (F(2, 42) = 37.301, p < .001, η² = .640). Post-hoc analysis revealed that both the forgiveness and mindfulness groups showed significant improvements in cognitive flexibility from pre-test to post-test (mean difference = -7.200, p < .001) and from pre-test to follow-up (mean difference = -7.244, p < .001), with no significant decline from post-test to follow-up (mean difference = -0.044, p = 1.00). For communication skills, significant improvements were also observed in both intervention groups from pre-test to post-test (mean difference = -17.311, p < .001) and pre-test to follow-up (mean difference = -17.533, p < .001), with no significant change from post-test to follow-up (mean difference = -0.222, p = 1.00). Mindfulness training demonstrated slightly higher effectiveness in improving communication skills compared to forgiveness training. Conclusion: Both forgiveness and mindfulness training significantly improved cognitive flexibility and communication skills in individuals with SUDs, with mindfulness training showing slightly greater effectiveness, particularly in communication skills. These findings suggest that integrating these interventions into treatment programs for SUDs can enhance critical cognitive and interpersonal functions, contributing to successful recovery and long-term well-being.